Lessons from foreign military surgeons in the Korean War: advancing trauma surgery and preparing for future conflicts - Hwang, Kun; Park, Chan Yong (Daehan oe'sang haghoeji, 2025)
Purpose: The Korean War (1950–1953) significantly advanced military medicine, with foreign military surgeons playing a pivotal role in transforming trauma care under extreme conditions.Methods: Resources such as PubMed, JSTOR, and reports from participating nations formed the basis of this study. A thorough comparative analysis was performed to examine the similarities and differences in medical practices between the United Nations Command and North Korean forces.Results: The United States introduced Mobile Army Surgical Hospitals, revolutionizing trauma care by enabling rapid intervention near combat zones. Innovations such as helicopter evacuation, whole blood transfusions, and antibiotic treatments reduced mortality rates among treated soldiers to as low as 3%. British surgeons excelled in managing abdominal wounds and performing orthopedic surgery, often undertaking limb-saving procedures. Field hospitals provided comprehensive care for combat injuries and infectious diseases—a major concern given the inadequate sanitation. The Indian 60th Parachute Field Ambulance treated over 20,000 casualties, demonstrating adaptability in harsh environments. The Indian Field Hospital not only treated military casualties but also provided care to Korean civilians, offering life-saving medical interventions under challenging conditions. Denmark deployed the hospital ship MS Jutlandia, equipped with advanced surgical facilities, enabling a level of medical care that was not practical on land. The Swedish Red Cross Field Hospital in Busan delivered crucial medical aid to both military personnel and civilians; its staff focused on civilian outreach and controlling epidemics, with treatments targeting diseases such as typhoid and tuberculosis. Norwegian mobile surgical teams specialized in rapid interventions near combat zones, performing life-saving operations within hours of injury and thus minimizing complications and increasing survival rates.Conclusions: The lessons learned from these contributions continue to influence modern military and civilian healthcare systems, highlighting the importance of innovation, collaboration, and resilience in conflict settings.